2014
DOI: 10.1016/j.jtbi.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies on the NMR and X-ray structures of rabbit prion proteins

Abstract: Prion diseases, traditionally referred to as transmissible spongiform encephalopathies (TSEs), are invariably fatal and highly infectious neurodegenerative diseases that affect a wide variety of mammalian species, manifesting as scrapie in sheep and goats, bovine spongiform encephalopathy (BSE or mad-cow disease) in cattle, chronic wasting disease in deer and elk, and Creutzfeldt-Jakob diseases, Gerstmann-Sträussler-Scheinker syndrome, fatal familial insomnia, and kulu in humans, etc. These neurodegenerative d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 135 publications
(179 reference statements)
1
15
0
Order By: Relevance
“…Similar studies comparing rabbit wild-type PrP and S173N and I214V mutated forms showed that either mutation significantly altered the salt bridge network and the hydrogen bond network, which increased structural instability. Thus, all these studies point toward distinctive intramolecular interactions being responsible for the stability of rabbit PrP, with a major contribution of the interactions established between the ␤2-␣2 loop and ␣-helices 2 and 3 (16,17,24). Importantly, these studies also reveal that point mutations can cause unpredictable changes in regions away from the mutation site itself.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar studies comparing rabbit wild-type PrP and S173N and I214V mutated forms showed that either mutation significantly altered the salt bridge network and the hydrogen bond network, which increased structural instability. Thus, all these studies point toward distinctive intramolecular interactions being responsible for the stability of rabbit PrP, with a major contribution of the interactions established between the ␤2-␣2 loop and ␣-helices 2 and 3 (16,17,24). Importantly, these studies also reveal that point mutations can cause unpredictable changes in regions away from the mutation site itself.…”
Section: Discussionmentioning
confidence: 88%
“…The generation of transgenic rabbits expressing ovine PrP and their successful infection with scrapie prions definitively highlighted that the amino acid sequence of rabbit PrP C was responsible for the low susceptibility of rabbits to prion infections (14). Although rabbit PrP C has been studied in detail to identify distinctive structural elements that explain its low susceptibility to prion-like misfolding (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), the key elements or amino acid residues causing this behavior remain unknown.…”
mentioning
confidence: 99%
“…Stabilizing long-range interactions between the β2-α2 loop and α-helix 3 also occur in rabbit PrP, a species generally regarded as resistant to prion infection (reviewed in ref. 20). X-ray crystallographic analyses showed the rabbit β2-α2 loop to be clearly ordered and indicated that hydrophobic interactions between the side chains of V169 and, in this case Y221 (elk PrP numbering) of α-helix 3, contributed to the stability of the β2-α2 loop/α helix 3 epitope (21) (Fig.…”
Section: Discussion Prp Polymorphisms Operate By Distinct Mechanisms mentioning
confidence: 99%
“…The MD methods employed are the same as the previous studies [Zhang & Zhang, 2013, Zhang & Zhang, 2014, Zhang, 2010. Briefly, all simulations used the ff03 force field of the AMBER 11 package [Case et al, 2010].…”
Section: Molecular Dynamics (Md) Techniquesmentioning
confidence: 99%